Structure and function of Pet100p, a molecular chaperone required for the assembly of cytochrome c oxidase in Saccharomyces cerevisiae. (August 2001) - Forsha, D.; Church, C.; Wazny, P.; Poyton, R. O.
Abstract : The assembly of cytochrome c oxidase in the inner mitochondrial membranes of eukaryotic cells requires the protein products of a large number of nuclear genes. In yeast, some of these act globally and affect the assembly of several respiratory-chain protein complexes, whereas others act in a cytochrome c oxidase-specific fashion. Many of these yeast proteins have human counterparts, which when mutated lead to energy-related diseases. One of these proteins, Pet100p, is a novel molecular chaperone that functions to incorporate a subcomplex containing cytochrome c oxidase subunits VII, VIIa and VIII into holo-(cytochrome c oxidase). Here we report the topological disposition of Pet100p in the inner mitochondrial membrane and show that its C-terminal domain is essential for its function as a cytochrome c oxidase-specific 'assembly facilitator'.